DEVELOPING LANGUAGE SCAFFOLDING MATERIALS FOR ARGUMENTATIVE WRITING: AN IDEA FOR TEACHING INTERMEDIATE WRITING SKILLS - Refnaldi Refnaldi (University of Muhammadiyah Purwokerto, 2010)
Materials are generally used to provide a stimulus to writing ordiscussion, as a starting point for language input and analysis, and asideas for organizing lesson activities. In EFL context, materials playparticular important roles because they may be the only contact thatlearners have with English and offer the only opportunities for them to study target texts. One of the important roles of instructionalmaterials is to provide the foundation for learners’ understandings ofwriting and language use. They are often used to present a focus forlanguage, such as to scaffold learners’ evolving control of differenttexts. Materials that assist learners toward producing clear andaccurate sentences and cohesive texts are obviously very importantwhen learning to write. This paper aims at discussing thedevelopment of language scaffolding materials in the writing activitywhich is based on the genre-based approach. “Scaffolding” in this case is the activity to provide any kind of support for students while they are establishing their understanding of a text and their linguistic competence to create the text. The materials provide input, tasks, and instruction that can be used to encourage and as well as to challenge students. The discussion will be focused on developing materials on four main steps of scaffolding for students of English Department. They are language familiarization, model analysis and manipulation, controlled composition, and guided composition.